Radiosurgical Options in Neuro-oncology: A Review on Current Tenets and Future Opportunities. Part I: Therapeutic Strategies. Issue 4 (July 2014) - Ganau, Mario; Foroni, Roberto Israel; Gerosa, Massimo; Zivelonghi, Emanuele; Longhi, Michele; Nicolato, Antonio
Stereotactic radiosurgery can nowadays be considered not only as a potential adjuvant to surgical treatment of several neuro-oncological pathologies, including primary tumors and metastatic lesions, but in some cases also as a valuable alternative tailored option. In Part I of the review, we propose a dissertation focused on the different irradiation stereotactic radiosurgery techniques to date available for clinical indications more relevant to oncologists and oncologic surgeons, such as high-grade and low-grade gliomas, metastases and meningiomas. It is noteworthy that the most recent body of literature correlated with this topic shows that the therapeutic results presently achievable are revolutionizing the way patients are diagnosed and managed worldwide. As we sought to shed light on the current potentialities of stereotactic radiosurgery, we must consider that to exploit all the benefits provided by this shift in clinical practice, a profound awareness by all practitioners involved in the care of neoplastic patients is certainly warranted.